Prevalence Of Anaemia and Visual Impairment Among School Going Adolescents of Patan City, Gujarat: A Cross Sectional Study - Sunil Nayak; Nilesh Thakor; Rajendra Gadhavi (Medsci Publications, 2015)
Background: Adolescence and young adulthood are periods of critical development and transition. Adolescent constitutes over 23% of the population in India. Nutrition and health needs of the adolescent are more because of more requirements for growth spurt and increase in physical activity. Objective: To study prevalence of anemia and visual impairment among school going adolescents of Patan city, Gujarat Methodology: The study was carried by Community Medicine Department, GMERS Medical College, Dharpur-Patan during period from September 2014 to August 2015. After taking the permission of principals of 9 schools and consent of the parents of adolescents, 841 adolescents from 10 schools of Patan city were examined for anemia and visual impairment. The data was col- lected by predesign, pretested proforma and analyzed using SPSS 17.0 (Trial Version) Results: Mean age was 15.8 ± 1.96 years. Out of 841, 432 (51.4%) were boys and 409 (48.6%) were girls. The study revealed that 67.0% girls were suffering from anaemia compare to 58.7% of boys. 117 (13.9%) adolescents had visual impairment. Conclusion: High prevalence of anemia and visual impairment among these adolescents needs great attention and health education.